Sistem Informasi Penjualan Berbasis Web dengan Metode Perpetual pada Aplikasi Website FURNIE - Aprilia Pramudita; Fajar Bagus Saputra; Miftahuda Adhananto; Vrisa Arana Salsabilla (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2025)
This study aims to design and develop a web-based sales information system for the Furnie application using a perpetual inventory recording method. The system is built using the Waterfall approach and technologies such as PHP, MySQL, and Laravel. The main goal is to improve transaction recording efficiency, inventory data accuracy, and support a more structured and responsive business process. The implementation results indicate that the system effectively facilitates product and order management, as well as automated reporting through a user-friendly interface. It also supports third-party service integration, notifications, and promotional features, contributing to enhanced user satisfaction. This approach positions Furnie as a suitable digital solution for modernizing furniture store operations in a more efficient and adaptive way.